The institutional framework of urban policy in Spain and comparative notes with Brazil - Goulart, Jefferson Oliveira [UNESP] (FapUNIFESP (SciELO), 2018)
The institutional framework of urban policy includes norms that regulate the actions of the State regarding land use, territorial planning and the competences of varying levels of government. In Spain, we have the central government, the comunidades autônomas (like the states in Brazil) and the ayuntamientos (local government). This analysis also includes the Ley de Suelo and Master Plans, taken as a privileged reference so that the study is not limited to the normative aspects of the institutional framework. Despite the differences and distinct aspects, this comparative analysis between Spain and the Urban Policy in Brazil allows us to identify common impasses, such as the hegemonic presence of a mercantile ideology of the city and urban management concepts that have spread the theses of urban entrepreneurship.
O marco institucional da política urbana na Espanha e apontamentos comparativos com o Brasil
Keywords: Brazil; Law of ground; Master plans; Spain; Urban policy